Structural design for passenger safety - Roots, Mark R. (Cranfield University, 1996)
This thesis covers the design and analysis of a roll cage structure for use on a sports racing car. The method used to design and verify the roll structure was novel as small automotive companies tend to use evolution as a design tool. Evolutionary design works well for certain problems, however, is not well suited to major structural modifications. The method used in this report integrates the existing structure with the roll cage to improve the torsion stiffness and hence the handling of the vehicle. Careful integration of the roll cage with the rest of the chassis enabled the torsion stiffness to be increased by over 400 %. In addition the weight efficiency of the final chassis was increased over that of the original chassis by over 200 % . The investigation of the torsion stiffness was carried out using linear finite element analysis using the NASTRAN suite of programs. The second stage of the investigation was to develop this design into a crashworthy roll cage. The resulting model and design are presented in this report. The design of the crashworthy roll cage was carried out using non linear finite element analysis with N AS TRAN. The N AS TRAN results were then verified with a full structural test on the chassis. The results of the tests are presented and compared to the NASTRAN analysis results. Good correlation was achieved and the method showed promise for applications in the small automotive industries. The use of finite element analysis for the design of an integrated structure represented a novel application of a well established technique to an industry where experience is the main design tool. The results of the investigation were encouraging and a close correlation was achieved between the analysis and test results. Finite element analysis represents a relatively cheap and quick method of investigating the effect of structural changes. This method could be used for the design and development of new structures and would give a good indication of the effect of these changes. Small automotive companies, such as TVR, should find the technique particularly useful for both the design of new structures and for the modification of those already in use.